WHAT DRIVES LOYALTY IN THE DIGITAL HOUSING MARKET? INSIGHTS FROM SOCIAL MEDIA MARKETING, CUSTOMER EXPERIENCE, AND PAYMENT EASE AMONG FIRST-TIME BUYERS - Abror; Yacob, Syahmardi; Dahmiri (Journal of Business Studies and Management Review, 2025)
This study examines the influence of Social Media Marketing, Purchase Experience, and Ease of Payment on Customer Satisfaction and Customer Loyalty among first-time homebuyers in Jambi City. As digitalization accelerates across Indonesia’s property sector, consumers rely increasingly on social media for information, and digital payment technologies have transformed transaction processes. A mixed-methods approach was adopted, combining quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) on 215 respondents with qualitative insights gathered through a Focus Group Discussion (FGD) involving property developers, banking institutions, industry associations, academics, and local government representatives. The findings indicate that all three exogenous variables significantly affect customer satisfaction and loyalty. Social media marketing enhances consumer trust through transparent digital information, while purchase experience significantly shapes satisfaction through responsive communication, clarity of administrative processes, and personalized assistance. Ease of payment emerges as the most influential driver of satisfaction, highlighting the rising consumer expectation for simplified, secure, and digitized mortgage and payment procedures. Customer satisfaction mediates the effects of the three exogenous variables on loyalty, demonstrating that emotional comfort and trust are key determinants of long-term consumer commitment. These findings provide strategic implications for property developers, financial institutions, and policymakers in strengthening marketing, service quality, and digital transformation within Indonesia’s evolving property market.